The Neverending Story: Illusions of Limitlessness and Abundance in the Metaverse - Hesselbein, Chris (Funes. Journal of narratives and social sciences, 2025)
This paper critically unpacks one central narrative feature of the Metaverse, namely its purported limitlessness, endlessness, and abundance, particularly on the level of spaces, objects, bodies, and identities. The primary means through which to present the Metaverse as limitless is by blurring the boundaries between the physical and virtual or the material and immaterial. Once these distinctions have been obscured, the apparent limitlessness of virtual phenomena can be positioned as surpassing the limits of material existence. The Metaverse can subsequently be presented as a world of near infinite possibilities, a future that is only limited by our imaginations. Narratives that represent the metaverse as endless and limitless are far from pointless; their apparent vagueness is precisely the point. Such narratives obscure the harmful actions of ‘Big Tech’ companies in the present, and mask the totalizing and all-encompassing character of the Metaverse as an attempt to reshape reality.